2012
DOI: 10.1177/000313481207800231
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocarcinoma: Aggressive Surgical Intervention Remains Justified

Abstract: Cholangiocarcinoma (CCA) continues to be a difficult disease to both diagnose and treat. Optimal treatment includes resection to histologically negative margins. In recent years, advanced imaging, including magnetic resonance cholangiography and endoscopic ultrasound, has presumably improved the accuracy of determining resectability. From 2004 to 2009, a total of 61 patients with cholangiocarcinoma were evaluated for resection. The majority were men (37) and ages ranged from 29 to 87 years (mean, 67 years). On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Efforts to elucidate the molecular mechanism underlying tumorigenicity and metastasis of CCA are urgently warranted to identify new biomarkers for prediction and intervention . Previous studies have intensively investigated the function of gankyrin as a component of proteasome complex in explaining its oncogenic activity .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to elucidate the molecular mechanism underlying tumorigenicity and metastasis of CCA are urgently warranted to identify new biomarkers for prediction and intervention . Previous studies have intensively investigated the function of gankyrin as a component of proteasome complex in explaining its oncogenic activity .…”
Section: Discussionmentioning
confidence: 99%
“…Cholangiocarcinoma (CCA) is the second most common primary hepatic malignancy after hepatocellular carcinoma (HCC) . Epidemiologic studies showed that the incidence and mortality rates of CCA are increasing in several Western countries, including the U.S . Unfortunately, CCA is characterized by a poor prognosis and a very low 5‐year survival rate .…”
mentioning
confidence: 99%
“…The patients were scheduled for chemoradiotherapy later. The prognosis for patients with cholangiocarcinoma arising in choledochal cysts is as grim as that for cholangiocarcinoma in general, with a median survival reported in the range of 6-21 months (30). Our patients in this study died one and three years, respectively, after the diagnosis.…”
Section: Discussionmentioning
confidence: 55%
“…Cholangiocarcinoma (CCA) is the second most common hepatobiliary malignancy, and its incidence has increased in recent years, with approximately 5,000 new cases in the United States per year 1 2 . Current therapeutic options for CCA are limited, and the overall prognoses for patients with CCA remain dismal 3 4 5 6 .…”
mentioning
confidence: 99%